Antisapasi Hoax Di Era Informasi: Pendidikan Karakter Perspektif Al-Qurán Surah Al-Hujurat Ayat 6: Antisapasi Hoax Di Era Informasi: Pendidikan Karakter Perspektif Al-Qurán Surah Al-Hujurat Ayat 6 - Zaini, Zaini (Perkumpulan Sarjana Pendidikan Islam Indonesia (PSPII) Wilayah Kalimantan Barat, 2021)
Today, information can be accessed from various facilities, ranging from paper, radio, and television to smartphones. The amount of information found everywhere makes some people accept a news without filtering the truth of the news. As a result of this people's inaccuracy, various false news circulating in this millennial era is called a hoax. Circulation of fraud among the people, especially in Indonesia is inevitable. Multiple cases have occurred. In fact, according to a survey conducted by Ricky Firmansyah in 2017, stated that hoax news in Indonesia has spread on internet sites by 34.9%, television 8.7%, print media 5%, email 3.7%, and radio 1.2%. Faced with these problems, it is important to look at the view of the Qur'an on the phenomenon of the spread of hoax news. Of course, there is no doubt that the Qur'an is in the highest believed position for the guideline of life for all mankind, especially Muslims. One solution offered by Al-Qur'an related to anticipating the spread of hoax news is the tabayyun attitude. This manner is noted in QS. al-Hujurat verse 6. It is a discipline to examine and select any report, not in a hurry in deciding issues of law, policy and so on until the problem is apparent. Although this term seems classic, but the terminology of tabayyun is more interesting and relevant in overcoming the existing problems, especially in the current information age.